Biotechnology-Derived, Perennial Turf & Forage Grasses: Criteria For Evaluation - Kenna, Michael; Hallman, William K.; Auer, Carol A.; Casler, Michael D.; Hopkins, Andrew; Karnok, Keith J.; Mallory-Smith, Carol; Shearman, Robert C.; Stier, John C.; Taliaferro, Charles M.; Yelverton, Fred (Council for Agricultural Science and Technology (CAST), 2004)
Following a 2-day workshop sponsored jointly by CAST and the U.S. Department of Agriculture-Animal and Plant Health Inspection Service, an 11-member task force undertook the writing of this publication to present in summarized form the contributions made by the diverse group of workshop participants, as well as those who submitted comments before and after the formal meetings. Major sections include: principles supporting ecological risk assessment and regulatory decision making; background information on perennial grasses; gene migration and weed management of biotechnology-derived (BD) perennial grasses; criteria for evaluating BD grasses; and a summary of workshop responses and public comments.